Knowledge spillovers from foreign direct invesments - Czech case study - Jan Stejskal; Abdelwalid Rouag (European Regional Science Association (ERSA), 2015)
The foreign direct investments (FDI) spillovers are probably the most extensively analyzed channel of knowledge spillovers (the most important channel for the transfer of knowledge and technology to firms of the host country). Scholars as well as policy makers increasingly treat FDI spillovers as very or the most important development effect for host country. However, whether this knowledge and technology are hypothesized to spill over depends on the absorptive capacity of the host country which stems from well-equipped human resources such as scientists and cumulative expenditure in research and development (R&D). In this paper, we examine for the single time the extent of knowledge spillovers and the absorptive capacity of the Czech Republic regions. Our empirical analysis is based on two main sources. First, the confidential micro-data derived from an annual census of R&D collected by the Czech statistical office with the collaboration of the Czech industrial property office. The data measures inputs in R&D such as the financial means and human resources in the entire entities that carry out R&D and their primary and secondary activities. The mico-data includes also indicators about the R&D outputs in the form of new knowledge used in several practical applications such as patents and utility models. The second source of Data consists on the inflow of FDI at the regional level. The data is collected and published by the Czech National bank according to the international standards adopted by the Organization for Economic Cooperation and development (OECD), European commission and the International Monetary Fund (IMF) data compilation of balance of payments. The paper finds that there is a significant knowledge inflow from the FDI to local firms. Our results state that coefficient of FDI inflows is always positive for both models so that the empirical evidence supports that FDI generates spillover effects on the domestic regional innovation capability of the Czech Republic. As advised by the literature, the spillover effects occur through the absorptive capacity such as the skilled labor turnovers and the R&D expenditure in both entrepreneurial and public sector. In this context, our two models suggest a positive impact of labor in private sector and even significant in both models for the public sector which highlights the important role played by universities, scientific institutes and NGOs. On the other hand, the correlation matrix of both patents application and utility models show a negative relation between two independent variables; FDI inflows and R&D government expenditure that fosters the assumption that the government expenditure in R&D crowds out the FDI inflow and hinder the beneficial effects of the latter.
Keywords: D83; D92; O11; 330; foreign Direct Investment; knowledge spillovers; absorptive capacity; patent app